Labeling PKI dan Dampaknya Terhadap Pemenuhan HAM Penghayat Kepercayaan Terhadap Tuhan Yang Maha Esa - Ceprudin Ceprudin; Retno Mawarini Sukmariningsih (Hukum dan Dinamika Masyarakat, 2024)
This study aimed to counter the narrative that has already spread wildly in the wider community that believers of unofficial religion (penghayat kepercayaan) to God Almighty (hereinafter written Belief) were identical to communist. This writing is important to reveal the real facts about the struggle around 1965 and its excesses against the existence of believers of unofficial religion (penghayat kepercayaan) in Indonesia. Even though decades have passed, the labeling as communist and non-religion, which was then followed by the misguided and deviated stigma until now it hasn't disappeared. For the groups of “penghayat kepercayaan”, this condition has left a deep trauma. Even though the government has issued a series of laws and regulations that sought to protect and fulfill the groups of “penghayat kepercayaan”, but it has not been able to completely cleared up the stigma of “non religion people - communist” which has widespread in society. This period was be recognized by “penghayat kepercayaan” was the toughest period in the Indonesian history. The label of communist made the “penghayat kepercayaan” fell out and not a few organizations of “penghayat kepercayaan” were be "apparent death" because their "congregations" have left them. Many Believers chose to adhere to a religion (even if it is only an identity) so that they could be safer from social pressures. Until now, some organizations of “penghayat kepercayaan” are still trauma, so that they have not freely expressed their beliefs as a “penghayat kepercayaan” in the public sphere. The actual fact is “penghayat kepercayaan” were an entity of the Nusantara community’s group which was completely different from communist. Even at one time, “penghayat kepercayaan” were politically confronted directly with communist groups at the political event in 1965. In reviewing this fact, the author would describe the research based on the facts that appeared or as they were. So, the type of this research used a Qualitative-empirical approach. The place of this research located in Central Java as the province that was in accordance to the data, in temporary it had the most of organization of “penghayat kepercayaan”. Sourced of data would be carried out randomly, namely from elders of the flow of belief's organization who experienced or witnessed the period around 1965. The author hypothesized that “penghayat kepercayaan” are victims of being labeled PKI